2001
DOI: 10.1603/0022-2585-38.5.746
|View full text |Cite
|
Sign up to set email alerts
|

The First Documented Forensic Entomology Case in Thailand

Abstract: The forensic entomology case described herein is the first such case documented in Thailand. A mummified corpse of a 32-yr-old man was discovered in a forested habitat, with the larvae of six species of flies (Diptera) found in association with the corpse at the time of its discovery, i.e., those of Hydrotaea (=Ophyra) spinigera Stein (family Muscidae), Piophila casei (L.) (family Piophilidae), Megaselia scalaris (Loew) (family Phoridae), Sagus sp. (family Stratiomyidae), and larvae of two unidenitified flesh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 9 publications
1
27
0
2
Order By: Relevance
“…Study on the mechanical carrier of bacterial enteric pathogens by C. megacephala in Chiang Mai province, northern Thailand showed a total of 39 bacterial species, with 8 groups isolated and three species previously reported as bacterial enteric pathogens that cause diarrheal diseases, including Aeromonas hydrophila, Edwardsiella tarda and Vibrio cholerae non-01 [39]. Nonfermentative gram-negative bacilli and coagulase-negative staphylococci were isolated from C. megacephala in urban areas of Chiang Mai [60] and this blow fly species was more potentially dangerous for public health than the house fly, Musca domestica [61]. Srivoramas et al, [45] recently confirmed that C. megacephala has the ability to function as a mechanical carrier of fungal spores and is able to transmit fungi to humans in Ubon Ratchathani province, northeastern Thailand.…”
Section: Medically-important Aspects Of the Blow Fly: Thailand Appraisalmentioning
confidence: 99%
See 2 more Smart Citations
“…Study on the mechanical carrier of bacterial enteric pathogens by C. megacephala in Chiang Mai province, northern Thailand showed a total of 39 bacterial species, with 8 groups isolated and three species previously reported as bacterial enteric pathogens that cause diarrheal diseases, including Aeromonas hydrophila, Edwardsiella tarda and Vibrio cholerae non-01 [39]. Nonfermentative gram-negative bacilli and coagulase-negative staphylococci were isolated from C. megacephala in urban areas of Chiang Mai [60] and this blow fly species was more potentially dangerous for public health than the house fly, Musca domestica [61]. Srivoramas et al, [45] recently confirmed that C. megacephala has the ability to function as a mechanical carrier of fungal spores and is able to transmit fungi to humans in Ubon Ratchathani province, northeastern Thailand.…”
Section: Medically-important Aspects Of the Blow Fly: Thailand Appraisalmentioning
confidence: 99%
“…Furthermore, a study revealed that insects associated with pig (Sus scrofa) carcasses in Thailand were found primarily in Phitsanulok province [71]. C. megacephala and A. rufifacies, are considered the most forensically-important blow fly species in the country [71][72][73][74][75]. Accordingly, the first documented case report in Thailand was published by Sukontason et al [72].…”
Section: Medically-important Aspects Of the Blow Fly: Thailand Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the flies have been reported from human cadavers (Nazni et al, 2008;Saigusa et al, 2003Saigusa et al, , 2006Sukontason et al, 2001Sukontason et al, , 2007. The larvae of the P. casei are found during the advanced decomposition phase of a cadaver, while the adult flies are typically observed beginning several days after death (Byrd and Castner, 2009).…”
Section: D>h8jhh>dcmentioning
confidence: 99%
“…Es así que la Entomología Forense representa una ayuda invaluable en casos de cuerpos muy descompuestos, como ocurre en las muertes por homicidio, muerte repentina como la anafilaxis por picadura de abeja o accidentes de tránsito, donde los restos humanos son colonizados por insectos [1,2,3]. El entomólogo forense participa en la identificación de los artrópodos y en el análisis de la data entomológica, en la interpretación de esta y así, contribuye con la determinación del tiempo o Intervalo Post-Mortem (I.P.M.…”
Section: Introductionunclassified